Описание личинок четырех видов пластинчатоусых жуков (Coleoptera, Scarabaeidae) из Грузии - Джамбазишвили, Я.С.; Медведев, С.И. (Вестник зоологии, 1974)
Larvae of Aphodius planicollis Men., Amphicoma arctos Pall., Ansioplia signata Fald., Tanyproctus persicus Fald. are described. They are compared with larvae of other species known before.